Impact of Managerial Skills on Organizational Development: An Applied Study in the Regional Directorate of Transport and Communications of the Amazonas Region - Salazar, Carlos Alberto Hinojosa; Pelaez , Heisely Mori; Escobar , Benjamín Roldan Polo; Meléndez , Milagros Natividad Hinojosa; Camacho , Consuelo González; Caballero , Ariadna Martínez (Journal of Ecohumanism, 2024)
This study analyzes the relationship between managerial skills and organizational development in the Regional Directorate of Transport and Communications of the Amazon Region during the year 2021. A quantitative approach with descriptive-correlational and non-experimental design was adopted, using a structured questionnaire applied to a sample of 72 workers. The results show that there is a low but significant positive evaluation between managerial skills (leadership, communication, decision making and motivation) and the dimensions of organizational development (planning, organization, integration and direction). The highest rating coefficient was Rho = 0.300, indicating a moderate relationship between managerial skills and overall organizational development. Although managerial skills influence process improvement and efficiency, other factors, such as organizational structure and available resources, also play a crucial role. It is concluded that it is essential to strengthen managerial competencies through continuous training programs and to improve internal processes in order to optimize organizational development in this public entity. Finally, it is suggested that other factors that may impact organizational development, such as technology and organizational culture, be explored in future studies.